Unravelling Power Relations in Sexual Violence in the Penyalin Cahaya Movie: Sara Mills' Feminist Stylistic Analysis Framework - Fira Fajria; Megasari Noer Fatanti (ARISTO, 2024)
The number of sexual violence cases against women in Indonesia almost reached 9,000 cases from January to November 2021. This number is increasing every year as protection against victims, whom predominantly are women, remains weak. All this time, social stigma has labeled women as victims since they are weak and easily oppressed. However, the reality of sexual violence does not only affect women but also men, who have long been regarded as the ruling group. In the Penyalin Cahaya movie, the issue of sexual violence is packed with different perspectives. The image of women as victims, who have been portrayed as a second class, weak, and confined group, is not seen in this film. Conversely, men as victims choose to shut up and surrender. This research aims to reveal the representation of sexual violence victims experienced by men and women using the framework of the Feminist Stylistics Approach/FSA developed by Sara Mills. The research body consists of scenes depicting (1) forms of sexual violence, (2) the social narrative of the victims and power relations in handling cases of sexual violence in academic environments, and (3) the representation of victims who choose to remain silent to stay accepted by the society. The documentation techniques were used to look more deeply into the positions and actions taken by the victims to fight the stigma caused by sexual violence. The research results show (1) the negation against male victims of sexual violence, (2) that women’s appearance still becomes the main reason for her to be harassed and (3) academic institutions are weak in dealing with sexual violence cases.